Study of Suppression of SC gap and 340 cm-1 Phonon in YBa2Cu3O7/La2/3Ca1/3MnO3 Superlattices - Omar Massoud Driza, Nadir (مجلة آفاق للدراسات الإنسانية والتطبيقية, 2024)
The main aim of this paper is to study the factors which effect on the B1g mode phonon of YBCO at the interface between the antagonistic materials YBCO and LCMO. Raman light scattering is the technique which used to perform this work. The Superlattices which studied are thin films of YBa2Cu3O7/La2/3Ca1/3MnO3 with different thickness. This study appears the shrinking of the SC-gap throw the 340 cm-1 due to the effect of the LCMO electrons which go through the YBCO and causes breaking of copper pairs, therefore it seems that the YBCO goes from the optimal doped case to the under doped case and that suppress the SC gap